Validity Test of Acupressure Digital Massage Tools (ADMT) on the Level of Comfort - Supriyadi Supriyadi; Sudirman Sudirman; Umi Margi Rahayu (GLOBAL HEALTH SCIENCE GROUP, 2024)
Comfort is the experience a person receives from an intervention. This is a direct and comprehensive experience when physical, psychospiritual, social, and environmental needs are met. Acupressure Digital Massage Tools (ADMT) is a modified tool that can be used on acupoints. This research is to determine the effectiveness of ADMT on comfort. This research is divided into 3 stages, namely stage 1 ADMT development, and validation, second stage ADMT tool application, and third stage production development. The research design for stage 1 is R&D and the second stage now uses a quantitative pre-post test design with a control group design. Samples were taken using a purposive sampling technique. The research subjects were 40 healthy respondents grouped into two, the first group was a sample of the healthy group with ADMT totaling 20 people and the second group was a sample of the healthy group with hand acupressure totaling 20 people, data analysis used demographic characteristics and research variables, namely ADMT and pain level. Bivariate analysis uses Wilcoxon and Mean Withney. The results of the information collection concluded that the ADMT action provided a feeling of comfort with validation that the respondents stated that they were comfortable by showing a feasibility score of 70%. Using Acupressure Digital Massage Tools (ADMT) is suitable as a tool for comfort levels.